Audit committee attendance and earnings management in Nigeria - Musa Nura, Dakata; Kamardin, Hasnah; Abdul Malak, Siti Seri Delima (2017)
Purpose- The aim of this study is to examine whether frequency of audit committee meetings and attendance in audit committee are associated with accrual earnings management.Design/methodology/approach- The sample of the study is 14 companies under the Industrial Goods sub-sector listed under the Nigerian Stock Exchange (NSE) for the years 2012-2014.Modified Jones Model (1995) was used to measure earnings management proxied by discretionary accruals. Findings- The findings show that frequency of audit committee meetings and attendance during the meetings negatively and significantly associated with discretionary accruals.Theoretical implications- This study extends the previous related literature by examining the association between audit committee meetings and attendance and earnings management.Practical implications- Regulators might use the findings of the study to regulate and further control the attendance of audit committee members during audit committee meetings.Originality/value- This paper uses agency theory to provide empirical evidence on the importance of frequent audit committee meetings and higher attendance in audit committee meetings.